2011
DOI: 10.4103/0255-0857.83910
|View full text |Cite
|
Sign up to set email alerts
|

Identification of plasmid-mediated quinolone resistance genes qnrA1, qnrB1 and aac(6’)-1b-cr in a multiple drug-resistant isolate of Klebsiella pneumoniae from Chennai

Abstract: Our report shows the prevalence of PMQR mediated by qnrA and qnrB in multidrug-resistant K. pneumoniae isolates from Chennai. A multidrug-resistant plasmid conferring high resistance to ciprofloxacin was found to harbour another PMQR gene, aac(6')-1b-cr mutant gene. This is the first report screening for PMQR in K. pneumoniae isolates from India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 20 publications
1
15
1
Order By: Relevance
“…In studies conducted by Lautenbach in USA (2001), Shahcheraghi (2007) in Iran and Tumbarello in Italy (2006), 60%, 48% and 32% of ESBL producing isolates of K. pneumoniae were resistant to ciprofloxacin, respectively (16-18). A report from India also showed that 61% of K. pneumoniae ESBL producers were resistant to ciprofloxacin and 52% to levofloxacin (19). Resistance to ciprofloxacin has also been observed in ESBL producing E. coli compared to non-ESBL isolates in Iran (10).…”
Section: Discussionmentioning
confidence: 99%
“…In studies conducted by Lautenbach in USA (2001), Shahcheraghi (2007) in Iran and Tumbarello in Italy (2006), 60%, 48% and 32% of ESBL producing isolates of K. pneumoniae were resistant to ciprofloxacin, respectively (16-18). A report from India also showed that 61% of K. pneumoniae ESBL producers were resistant to ciprofloxacin and 52% to levofloxacin (19). Resistance to ciprofloxacin has also been observed in ESBL producing E. coli compared to non-ESBL isolates in Iran (10).…”
Section: Discussionmentioning
confidence: 99%
“…Despite such high fluoroquinolone resistance rates, fewer than ten studies from India have reported the prevalence of PMQR genes. ( Pazhani et al, 2011 ; Geetha et al, 2014 ; Magesh et al, 2011 ; Bhattacharya et al, 2011 ). Data analysis in the diagnostic microbiology laboratory attached to Jawaharlal Institute of Postgraduate Medical Education & Research (JIPMER), Puducherry, India, a teaching hospital with a bed strength of 1,500, revealed 75% of the Enterobacteriaceae isolates to be resistant to ciprofloxacin in the year 2012 (T Yugendran, 2013, unpublished data).…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Andrea Endimiani et al have reported quinolone resistance due to qnr B and aac (6')-Ib gene in Klebsiella pneumoniae [25]. In a South Indian study, prevalence of PMQR mediated by qnrA (48%) and qnr A and qnr B (24%) in multidrug-resistant K. pneumoniae isolates have been reported [26].…”
Section: Discussionmentioning
confidence: 99%